Axonal damage in central and peripheral nervous system inflammatory demyelinating diseases: common and divergent pathways of tissue damage. Issue 3 (June 2016) - Barnett, Michael H.; Mathey, Emily; Kiernan, Matthew C.; Pollard, John D.
Abstract : Purpose of review: Axonal injury is the pathological correlate of fixed disability in the inflammatory demyelinating disorders of the central and peripheral nervous system. The mechanisms that initiate and propagate neurodegeneration in these conditions are poorly understood, and a lack of available neuroprotective and proreparative therapies represent a significant unmet clinical need. In this article, we review new data pertaining to the convergent and divergent immunological, cellular, and molecular mechanisms that underpin neurodegeneration in multiple sclerosis and the chronic inflammatory demyelinating neuropathies that will inform the development of targeted therapies. Recent findings: New insights have been gained from recognition of the axon as an integral component of the axon-myelin unit, identification of defects in axonal transport, elucidation of mechanisms of Wallerian degeneration and, in the central nervous system, the appreciation of trans-synaptic axonal degeneration, and widespread cortical synaptopathy. Concurrently, specific immune triggers of axonal injury, particularly in the peripheral immune system; and inhibitors of repair and regrowth, have been identified. Summary: Neurodegeneration is a critical determinant of disability in the inflammatory demyelinating diseases of both the central nervous system and peripheral nervous system. Current therapies are restricted to agents that (effectively) treat the inflammatory components of these conditions. Although propagated, and in some instances triggered, by inflammation, axon damage will in future years be treated or prevented with adjuvant, targeted therapies that exploit emerging pathways to neurodegeneration.